DAMPAK PENERAPAN NET ZERO EMISSION TERHADAP PERTUMBUHAN FISKAL INDONESIA - Cahyaputra, Vincent Adyan; Mukhlis, Rizka Amalia; Elizabeth, Irene; Sihaloho, Estro Dariatno (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2024)
This study has three objectives. First, to estimate the factors affecting the level of energy consumption, especially coal subject to carbon tax. Second, to project the amount of carbon emissions from 2020 to the year of carbon tax implementation (2025) using the Vector Error Correction Model (VECM). Third, to calculate the potential government revenue from the implementation of carbon tax starting from the year of carbon tax implementation (2025) until 2050. This study uses panel data of 33 provinces in Indonesia from 2021 to 2022 and time series data of Indonesia from 1990 to 2020. Research results from Indonesian panel data show that Gross Regional Domestic Product (GRDP) and GRDP per capita have a significant positive influence. The VECM analysis projects that the amount of CO₂ carbon emissions moves dynamically in the 2021 to 2025 time series. The results are then used in the projection of government revenue for the next 25 years with potential government revenue through carbon tax amounting to 6.6 trillion rupiah.